Revision of the Neotropical species of Aphilodontinae (Geophilomorpha, Geophilidae), with eight new species and a first phylogenetic analysis of the subfamily - Calvanese, Victor C.; Brescovit, Antonio D.; Bonato, Lucio (Zootaxa, 2019)
Aphilodontinae are a well distinct but poorly known group of soil centipedes (Chilopoda: Geophilomorpha: Geophilidae) inhabiting two disjunct areas in South America and South Africa respectively. A comprehensive revision of the Neotropical species is presented based on the examination of >150 specimens, the phylogenetic analysis of the entire subfamily based on 47 morphological characters, and the description of eight new species from Southeastern Brazil. The Aphilodontinae were confirmed a monophyletic clade within Geophilidae and closely related to Geoperingueyia, with which they share synapomorphic characters in the labrum, second maxillae and forcipules. Particular groups of clypeal setae, inconspicuous lateral parts of labrum and coalescent forcipular throchanteroprefemur and femur were recovered as synapomorphies of the Aphilodontinae. Four monophyletic genera are recognized within the subfamily Aphilodontinae Silvestri, 1909 (1908) (= Brasilophilidae Verhoeff, 1908; = Mecistaucheninae Verhoeff, 1925 n. syn.), three exclusively Neotropical and one exclusively South African. The Neotropical genera are: Aphilodon Silvestri, 1898 (= Mecistauchenus Brölemann, 1907 n. syn.; = Brasilophilus Verhoeff, 1908 n. syn.), with ten species (including A. caboclos n. sp., A. indespectus n. sp., A. meganae n. sp., A. pereirai n. sp. and A. silvestrii n. sp.), characterized by a small terminal spine on the ultimate legs, in both males and females; Mecophilus Silvestri, 1909, with two species (including M. tupiniquim n. sp.), characterized by elongated forcipular segment and first leg-bearing segment; Mairata n. gen., with two species (M. butantan n. sp. and M. itatiaiensis n. sp.), characterized by the partial reduction of the distal article of the second maxillary telopodite and a particular shape of ultimate legs, in both males and females. The South African genus, Philacroterium Attems, 1926, comprises eleven known species (including P. weberi (Silvestri, 1909) n. comb., P. caffrarium (Verhoeff, 1937) n. comb., P. porosum (Verhoeff, 1937) n. comb., P. brevipes (Verhoeff, 1938) n. comb., P. bidentatum (Lawrence, 1955) n. comb., P. longipes (Lawrence, 1955) n. comb., P. macronyx (Lawrence, 1955) n. comb., P. maritimum (Lawrence, 1963) n. comb., P. pauciporum (Lawrence, 1963) n. comb. and P. transvaalicum (Lawrence, 1963) n. comb.) and is characterized by vestigial lateral parts of the labrum and the complete suppression of the distal article of the telopodites of the second maxillae. Identification keys are provided for the Aphilodontinae genera and for the species of Aphilodon, Mecophilus and Mairata n. gen. The known occurrence of Aphilodon in Brazil is extended from the states of São Paulo and Mato Grosso to the states of Minas Gerais and Rio de Janeiro, that of Mecophilus from the state of Paraná to the state of São Paulo.